2019
DOI: 10.5032/jae.2019.01059
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Agricultural Mechanics Knowledge and Skills Needed by Iowa School-based Agricultural Education Teachers

Abstract: A historical portion of many school-based agricultural education (SBAE) programs, agricultural mechanics remains popular in schools across the nation. As such, pre-service and in-service teachers should be prepared to effectively deliver agricultural mechanics instruction (Burris, Robinson, & Terry, 2005). Agricultural education researchers Pate, Warnick, & Meyers, 2012) have identified many laboratory management competencies and welding skills that teachers should have; however, few knowledge and skill areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…These results are encouraging, as preservice teachers sometimes struggle with the complexities of teaching agricultural mechanics (Tummons et al, 2017). Agricultural mechanics is broad (Hainline & Wells, 2019), in-depth, and popular in many SBAE programs (Burris et al, 2005). Thus, it is imperative preservice teachers continue to be exposed to positive experiences related to agricultural mechanics, particularly within agricultural teacher preparation programs (Burris et al, 2005).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 97%
See 3 more Smart Citations
“…These results are encouraging, as preservice teachers sometimes struggle with the complexities of teaching agricultural mechanics (Tummons et al, 2017). Agricultural mechanics is broad (Hainline & Wells, 2019), in-depth, and popular in many SBAE programs (Burris et al, 2005). Thus, it is imperative preservice teachers continue to be exposed to positive experiences related to agricultural mechanics, particularly within agricultural teacher preparation programs (Burris et al, 2005).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 97%
“…Thus, instruction in agricultural mechanics is common (Burris et al, 2005). As a curriculum area, agricultural mechanics can include a variety of topics, including safety, small gas engines, welding and metal fabrication, electricity, carpentry and woodworking, advanced technologies such as global positioning systems (GPS), and more (Burris et al, 2005;Hainline & Wells, 2019;Shultz et al, 2014). Regarding the educational value and utility of this curriculum area, agricultural mechanics can serve as a useful, practical, and handson context for academic content instruction and reinforcement (Parr et al, 2006), problem-solving (Pate & Miller, 2011), and hypothesis generation (Blackburn & Robinson, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agricultural mechanics courses are traditionally taught within many SBAE programs (Burris et al, 2005;Phipps et al, 2008) and are popular choices for many students (Valdez & Johnson, 2020). Teaching agricultural mechanics courses requires that SBAE teachers have knowledge and skills in numerous topics, such as maintaining power equipment, teaching students how to properly perform welding procedures, and safely performing agricultural mechanics activities (Albritton & Roberts, 2020;Hainline & Wells, 2019). Scholars (Chumbley et al, 2018;Dyer & Andreasen, 1999;McKim & Saucier, 2011a;McKim & Saucier, 2012;Saucier et al, 2014) have indicated SBAE teachers must competently provide safe environments for effective agricultural mechanics instruction to take place.…”
Section: Introductionmentioning
confidence: 99%